Complete mitochondrial genome and phylogenetic analysis of Penicillium citrinum in dark tea. Issue 2 (3rd July 2019) - Hu, Zhiyuan; Shiquan, Liu; Xu, Zhenggang; Dong, Meng; Liu, Suchun
Abstract: Penicillium citrinum is a common polluting microorganism in dark tea production. Our study was performed to report the complete mitochondrial genome of P. citrinum . The mitochondrial genome of P. citrinum was a circular DNA molecule of 27, 537 bp in length, encoding 42 genes as follows: 15 PCGs, two rRNAs, 24 tRNAs, and an independent ORF. A (36.14%), T (37.06%), C (11.83%), and G (14.98%) was composed of genomic bases. In addition, phylogenetic analysis showed that Penicillium sp. exhibited a closest relationship with the taxonomic status of P. citrinum .